Multisystem inflammatory syndrome in children during the first two years of the COVID-19 pandemic in Luxembourg - Ooms, C.; Mossong, J.; Vergison, A.; Biver, A.; Wagner, K.; Niel, O.; Parrish, A.; Abdelrahman, T. T.; de la Fuente Garcia, I. (Frontiers in Pediatrics, 2023)
Objective: Estimate the incidence of multisystem inflammatory syndrome (MIS-C) in children (0-15 years), the role of SARS-CoV-2 variants during the first two years of COVID-19 pandemic in Luxembourg; and describe the demographic, biological and clinical characteristics of the patients. Method: Observational retrospective cohort study. Cases between March 2020 and February 2022 were ascertained from the national registry of MIS-C cases by a retrospective review of medical records. Reported SARS-CoV-2 infections were obtained from the national COVID-19 surveillance system. We calculated monthly MIS-C incidence, the ratio between MIS-C and SARS-CoV-2 infections and associated rate ratios by the periods corresponding to the circulation of different variants. Results: 18 children were diagnosed with MIS-C among 35200 reported infections. The incidence rate of MIS-C was 7.2 (95% confidence interval (CI) 4.5-11.4) per 1,000,000 person-months. A higher incidence of MIS-C was observed between September and December 2021, corresponding to the circulation of the Delta variant than during the first year of the pandemic (RR 3.6, 95% CI 1.1-12.3). The lowest rate of MIS-C per infection was observed during the Omicron (RR 0.17, 95% CI 0.03-0.82). Median age at diagnosis was 6.5 years. Previously healthy children made up 88% of MIS-C cases, none were vaccinated against SARS-CoV-2. 33% required intensive care. All patients recovered fully. Conclusions: MIS-C incidence and MIS-C risk per infection changed significantly over time during the first two years of COVID-19 pandemic. Monitoring of MIS-C incidence in future SARS-CoV-2 waves will be essential to guide public health interventions and vaccination policies for children.